The effect of chromium on photosynthesis and lipid accumulation in two chlorophyte microalgae - Bashir, Khawaja Muhammad Imran; Lee, Hyeon-Jun; Mansoor, Sana; Jahn, Alexander; Cho, Man-Gi (Energies, 2021)
Heavy metals have adverse effects on microalgae metabolism and growth. Photosynthesis and lipid profile are quite sensitive to heavy metal toxicity. The impact of hexavalent chromium— Cr(VI) on photosynthesis and lipid accumulation in Mucidosphaerium pulchellum and Micractinium pusillum exposed to different concentrations (0–500 µg L−1) was investigated for 11 days. A significant (p < 0.05) increase in lipid content was observed with increasing Cr(VI) concentration. However, growth was suppressed at higher concentrations exceeding 100 µg L−1. Addition of Cr(VI) in the cell culture medium showed a negative effect on quantum yield (Fv /Fm), and a photosynthetic inhibition of >65% was noted in both species at 500 µg L−1. However, the lipid gravimetric analysis presented inner cell lipid content up to 36% and 30% of dry weight biomass for M. pulchellum and M. pusillum, respectively. The fatty acids profiles of both microalgae species showed higher levels of hexadecenoic acid as well as ω3, ω6, and ω7 fatty acids. The effect of Cr(VI) on photosynthesis and lipid accumulation in both microalgae species was concentration and exposure time dependent. This shows that an appropriate concentration of Cr(VI) in culture medium could be beneficial for higher lipid accumulation in freshwater eukaryotic microalgae species.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Fatty acids; Freshwater microalgae; Growth kinetics; Heavy metal; Micractinium pusillum; Mucidosphaerium pulchellum; Photosynthesis; Toxicity